2012
DOI: 10.1258/phleb.2012.011125
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of current sonographic criteria for the detection of outflow abnormalities in the internal jugular veins

Abstract: Our research has shown that currently used extracranial sonographic criteria for the detection of obstructive venous abnormalities in the IJVs are of limited diagnostic value. For the time being, diagnosis of this vascular pathology should be given using catheter venography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
27
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 43 publications
(58 reference statements)
2
27
0
Order By: Relevance
“…The prevalence of these lesions was over 50% 32,33 and was even higher (about 90%) when more liberal definition of an abnormality or IVUS were used. 1,[20][21][22][23][24][25][26][27]104 Similarly, the results of MRV studies were quite consistent, ie, IJV stenoses were found in 25%-70% of patients with multiple sclerosis, 30,32,36,37,39,40,44,46,49 which is comparable with the results of catheter venography. A lower frequency of IJV abnormalities revealed by MRV probably resulted from the fact that this imaging modality cannot precisely assess the jugular valve, which is the most common site of CCSVI pathology.…”
supporting
confidence: 59%
See 4 more Smart Citations
“…The prevalence of these lesions was over 50% 32,33 and was even higher (about 90%) when more liberal definition of an abnormality or IVUS were used. 1,[20][21][22][23][24][25][26][27]104 Similarly, the results of MRV studies were quite consistent, ie, IJV stenoses were found in 25%-70% of patients with multiple sclerosis, 30,32,36,37,39,40,44,46,49 which is comparable with the results of catheter venography. A lower frequency of IJV abnormalities revealed by MRV probably resulted from the fact that this imaging modality cannot precisely assess the jugular valve, which is the most common site of CCSVI pathology.…”
supporting
confidence: 59%
“…19 Most of the studies that utilized catheter veno graphy have revealed pathologic venous flow in 95%-100% of patients with multiple sclerosis (Figure 1). 1,[20][21][22][23][24][25][26][27] Importantly, intravascular ultrasound (IVUS) was found to be very helpful as an adjunct to catheter venography. A combination of venography and IVUS provides a comprehensive assessment of venous anatomy, endoluminal structures, and flow.…”
Section: Results Of Catheter Venography and Ivusmentioning
confidence: 99%
See 3 more Smart Citations